Androgen Responses during Physical Exercise. Issue 5852 (3rd March 1973) - Sutton, J. R.; Coleman, M. J.; Casey, J.; Lazarus, L.
Abstract : The serum androgen response to physical exercise was studied in highly trained athletes and in normal male medical students. Serum androgens rose in response to maximal exercise and the rise was independent of serum luteinizing hormone. No response was obtained with submaximal exercise.